Analyzing Leak Detection Methods for Aluminum Cast Components in Automotive Manufacturing Processes - Abdur Rohman HM; Noval Lilansa; Ivan Tovani (Eduvest - Journal of Universal Studies, 2024)
This study was conducted to detect leaks in aluminum casting components in the automotive manufacturing process, which is a significant issue because it can affect vehicle safety. The method used in this study is the Cosmo Air Leak Tester for leak testing using air pressure and differential methods, as well as bubble test testing as an alternative method. The results of the study show that the air leak tester machine has stable values but cannot detect leaks caused by deformation. Changes in parameters on the Cosmo Air Leak Tester do not significantly affect bubble detection. On the other hand, the water leak method proved effective in detecting early leaks with the appearance of bubbles in products experiencing deformation up to 40 microns